2012
DOI: 10.1155/2012/234812
|View full text |Cite
|
Sign up to set email alerts
|

L(+) and D(-) Lactate Are Increased in Plasma and Urine Samples of Type 2 Diabetes as Measured by a Simultaneous Quantification of L(+) and D(-) Lactate by Reversed-Phase Liquid Chromatography Tandem Mass Spectrometry

Abstract: Background. Plasma and urinary levels of D-lactate have been linked to the presence of diabetes. Previously developed techniques have shown several limitations to further evaluate D-lactate as a biomarker for this condition.Methods. D- and L-lactate were quantified using ultraperformance liquid chromatography tandem mass spectrometry with labelled internal standard. Samples were derivatized with diacetyl-L-tartaric anhydride and separated on a C Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 35 publications
5
48
0
Order By: Relevance
“…High performance liquid chromatography (HPLC) (Gómez-Mingot et al 2012), mass spectrometry (MS) (Scheijen et al 2012) or nuclear magnetic resonance (NMR) , are well established techniques employed for the detection and quantification of lactate present in human embryo culture cells and generally biological systems; however, such techniques are costly and possess the inability for real-time or in-situ measurements.…”
Section: Introductionmentioning
confidence: 99%
“…High performance liquid chromatography (HPLC) (Gómez-Mingot et al 2012), mass spectrometry (MS) (Scheijen et al 2012) or nuclear magnetic resonance (NMR) , are well established techniques employed for the detection and quantification of lactate present in human embryo culture cells and generally biological systems; however, such techniques are costly and possess the inability for real-time or in-situ measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In another study of 263 non-obese (BMI approximately 24 kg/m 2 ) Asian–Indian and Chinese men, Tai et al [21] reported that pyruvate and lactate concentrations were increased in urine in the high-HOMA individuals of both ethnic groups; these changes were accompanied by significant increases in blood lactate concentrations as a function of HOMA, again in both ethnic groups. This is potentially exaggerated in T2DM patients [23]. β-Hydroxybutyrate is a classic ketone body found alongside acetone and acetoacetate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some [1823], but not all, studies [14] of organic acid profiles among humans have documented alterations of circulating or urinary organic profiles associated with insulin resistance, hyperglycemia or type 2 diabetes (T2DM). Some investigators have suggested that quantitative profiling of organic acids in urine may be a simple, sensitive test that can reveal evidence of functional inadequacy of specific nutrients for laboratory evaluations in insulin resistance and T2DM [21].…”
Section: Introductionmentioning
confidence: 99%
“…Urine d-lactate, the metabolite of MGO excreted in urine, may proxy for MGO and carbonyl stress, and it may be considered an early marker of diabetic injury [37]. The analytical methods used in the determination of d-lactate use HPLC [37] and liquid chromatography tandem mass spectrometry [73]. However, a newly developed d-lactate assay system, using d-lactate dehydrogenase to catalyze d-lactate and detect the catalysis with a UV-light-emitting diode, was reported recently [74].…”
Section: Methylglyoxal Usage In Clinical Settingsmentioning
confidence: 99%